Perovskite thin film and preparation and application thereof
Through the use of amino acids and lead iodide reactions during the preparation of the perovskite film to form an amorphous leading film, solve the problem of thin film defects caused by the iodide layer in the traditional method to obstruct the penetration of organic ammonium salts, and achieve the perovskite High stability and efficiency of mineral film.
Patent Information
- Application Number
- CN202411872274.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-21
AI Technical Summary
The stability problems of perovskite films limit their large-scale application, especially because the dense lead iodide layer in the traditional two-step process hinders the full penetration of organic ammonium salts, resulting in a large number of defects in the film.
By dissolving lead and amino acids in organic solvents, the front -drive body solution is formed, coated on the substrate for heat treatment, obtained an amorphous iodide film, and then coated with organic halide ammonium salt solution and perform secondary heat treatment. Forms perovskite film.
This method effectively reduces the diffusion resistance, promotes the uniform growth of the perovskite film and the quality of high crystallization, reduces the flaws of the film, improves its stability, thereby improving the performance and stability of the perovskite solar cell.
Smart Images

Figure CN119343025A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new photovoltaic materials, and in particular to a perovskite film and its preparation and application. Background Art
[0002] Perovskite solar cells have excellent photoelectric conversion efficiency. However, the stability of perovskite films has always been the main bottleneck restricting their large-scale application. At present, the preparation of perovskite films mainly adopts one-step method and two-step method. Among them, the two-step method has been widely studied because it can better control the crystallization process of perovskite. However, the dense lead iodide layer (PbI 2 ) hinders the full penetration of organic ammonium salts, resulting in a large number of defects in the perovskite film, such as grain boundaries, vacancies, etc. These defects accelerate the decomposition of perovskite materials.
[0003] In order to obtain high-quality perovskite films, the related technologies have been improved by solvent engineering or crystal-assisted growth. 2 However, these methods introduce anisotropic crystal structures of PbI 2 There is still a diffusion barrier that limits the penetration of organic ammonium salts, resulting in high diffusion resistance and crystalline PbI 2 The incomplete reaction with organic ammonium salts results in many defects and poor stability in the perovskite film, which seriously restricts the device performance.
[0004] Therefore, it is necessary to provide a preparation scheme for perovskite films so that the perovskite films have fewer defects and higher stability. Summary of the invention
[0005] In view of this, the present application provides a perovskite film and its preparation and application, which are used to solve the problem of how to improve the stability of the perovskite film.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing a perovskite film, comprising the following steps: S1. dissolving lead iodide and amino acid in an organic solvent to obtain a precursor solution; S2. coating the precursor solution on a substrate and performing a heat treatment to obtain an amorphous lead iodide film; S3. Apply an organic halide ammonium salt solution on the surface of the amorphous lead iodide film and perform a secondary heat treatment to obtain a perovskite film.
[0007] Preferably, the amino acids include one or more of alanine, valine, leucine, phenylalanine, serine, threonine, asparagine, glutamic acid, lysine, arginine, histidine, L-cysteine, glycine, and isoleucine.
[0008] Preferably, the organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0009] Preferably, the molar ratio of amino acid to lead iodide is 0.3:1-3:1.
[0010] Preferably, the temperature of the primary heat treatment is 160-400° C., and the time of the primary heat treatment is 10-300 min.
[0011] Preferably, the temperature of the secondary heat treatment is 60-180° C., and the time of the secondary heat treatment is 10-300 min.
[0012] Preferably, the organic halide ammonium salt includes one or more of formamidine hydroiodide (FAI), methylammonium bromide (MABr), and methylammonium chloride (MACl).
[0013] In a second aspect, the present application provides a perovskite film.
[0014] In a third aspect, the present application provides a perovskite solar cell comprising a perovskite film, which includes a bottom electrode, a hole transport layer, a perovskite film, an electron transport layer, a blocking layer and a metal electrode stacked in sequence.
[0015] Preferably, the hole transport layer comprises a nickel oxide layer; the electron transport layer is a carbon 60 (C60 layer) with a thickness of 10-50 nm; the barrier layer is a bathocuproine (BCP) with a thickness of 2-30 nm; and the metal electrode is Ag and / or Cu with a thickness of 80-180 nm.
[0016] The beneficial effects of the present application are as follows: by adopting amorphous lead iodide, the problem of many defects and poor stability of perovskite films caused by incomplete reaction of traditional crystalline lead iodide and organic ammonium salts is effectively solved, and the obtained perovskite film has high density and low defects, thereby improving the performance and stability of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Flow chart for preparing dense perovskite films for this application; Figure 2 SEM surface images of different perovskite films; Figure 3 Time-steady PL spectra of different perovskite films; Figure 4 is the photoelectric efficiency retention rate of different perovskite solar cells. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The present application provides a method for preparing a perovskite film, comprising the following steps: S1. dissolving lead iodide and amino acid in an organic solvent to obtain a precursor solution; S2. coating the precursor solution on a substrate and performing a heat treatment to obtain an amorphous lead iodide film; S3. Apply an organic halide ammonium salt solution on the surface of the amorphous lead iodide film and perform a secondary heat treatment to obtain a perovskite film.
[0020] This application prepares perovskite films based on amorphous lead iodide and constructs amorphous PbI 2 The matrix is used to reduce diffusion resistance and promote the uniform growth of perovskite film, thereby improving the stability of the device. The specific process is: first, amino acids are used to react with lead iodide to form an amorphous state (amino acid) 2 PbI 2 Template, after annealing to vaporize the amino acid, leaving porous amorphous PbI 2 matrix, which effectively reduces the diffusion resistance between lead iodide and organic ammonium salt, and promotes the uniform growth and high crystal quality of perovskite films.
[0021] In some embodiments, the amino acid comprises one or more of alanine, valine, leucine, phenylalanine, serine, threonine, asparagine, glutamic acid, lysine, arginine, histidine, L-cysteine, glycine, and isoleucine.
[0022] The amino acid of the present application reacts with lead iodide to generate an amorphous (amino acid) 2 PbI 2 After high-temperature annealing, the amino acid volatilizes, leaving an amorphous lead iodide skeleton with an interconnected nanopore structure. This skeleton significantly reduces the energy barrier for the reaction of organic halide ammonium salts with lead iodide, prompting the organic halide ammonium salts to quickly penetrate through the nanopores and fully react with the skeleton, ultimately forming a dense, highly crystalline perovskite film. Due to the low defect density and low lattice stress, the resulting perovskite film exhibits excellent stability, thereby improving the efficiency and life of the device.
[0023] In some embodiments, the organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0024] In some embodiments, the molar ratio of amino acid to lead iodide is 0.3:1-3:1.
[0025] In some embodiments, the temperature of the primary heat treatment is 160-400° C., and the time of the primary heat treatment is 10-300 min.
[0026] In the present application, the purpose of the primary heat treatment is to sublime the amino acid and obtain an amorphous lead iodide film having interpenetrating nanopores.
[0027] In some embodiments, the temperature of the secondary heat treatment is 60-180° C., and the time of the secondary heat treatment is 10-300 min.
[0028] In the present application, the purpose of the secondary heat treatment is to react the organic halide ammonium salt with lead iodide to form a perovskite film.
[0029] In some embodiments, the organic halide ammonium salt includes one or more of FAI, MABr, and MACl.
[0030] The present application provides a perovskite film.
[0031] The present application provides a perovskite solar cell comprising a perovskite film, which comprises a bottom electrode, a hole transport layer, a perovskite film, an electron transport layer, a barrier layer and a metal electrode stacked in sequence.
[0032] In some embodiments, the hole transport layer includes a nickel oxide layer; the electron transport layer is a C60 layer with a thickness of 10-50 nm, which is prepared by physical vapor deposition; the blocking layer is a BCP with a thickness of 2-30 nm, which is prepared by physical vapor deposition; the metal electrode is Ag and / or Cu with a thickness of 80-180 nm, which is prepared by physical vapor deposition.
[0033] In some embodiments, the hole transport layer is nickel oxide, which is prepared by a spray coating method. The preparation method is as follows: nickel acetylacetonate is dissolved in a mixed solution of acetonitrile and ethanol, and deposited on a conductive glass coated with fluorine-doped indium tin oxide FTO by spray pyrolysis, and annealed for 20-180 minutes to obtain a 10-50 nm thick dense layer of nickel oxide.
[0034] The present application introduces amino acids as templates, and applies (such as spin coating, scraping, or spraying) a mixed solution of amino acids and lead iodide on a substrate, and forms an amorphous lead iodide intermediate layer with a nanopore structure after heat treatment. Subsequently, an organic ammonium salt solution is infiltrated or coated on the intermediate layer, and the organic halide ammonium salt reacts with the lead iodide through the nanopores to finally form a dense perovskite film. The method of the present application has the advantages of universality and good repeatability, and the preparation process is simple, which is conducive to the large-scale production of perovskite photovoltaic materials.
[0035] The present solution is further described below through specific embodiments.
[0036] Example 1 A method for preparing a perovskite film comprises the following steps: S1. Weigh 157.6 mg of serine and 691.5 mg of lead iodide powder respectively, dissolve them in a mixed solution of 800 μL of DMF and 200 μL of DMSO, and continue to oscillate on an oscillator for more than 2 hours to completely dissolve them to obtain a precursor solution; S2. The precursor solution is coated on the FTO|NiO substrate at a coating speed of 10 mm / s and a distance between the blade and the substrate of 150 μm. Then, the substrate coated with the precursor is annealed on a hot plate at 250°C for 20 min to sublimate serine, thereby obtaining a loose disk-shaped amorphous lead iodide film with interpenetrating nanopores, namely, an amorphous lead iodide film; S3. Weigh 158.8 mg of FAI, 18.5 mg of MABr and 18.2 mg of MACl powder respectively, dissolve them in 1 mL of IPA solution, and continue to oscillate in an oscillator for 25 min to completely dissolve them to obtain an organic halide ammonium salt solution. Apply the organic halide ammonium salt solution on the amorphous lead iodide film at a coating speed of 15 mm / s and a distance of 200 μm between the blade and the substrate. Then, anneal the substrate on a hot plate at 150°C for 30 min to obtain a perovskite film.
[0037] Example 2 A perovskite solar cell, whose structure is FTO|NiO|perovskite layer|C60:BCP|Ag; the perovskite layer is the perovskite film of Example 1.
[0038] The preparation method of the perovskite solar cell of this embodiment: The laser-etched FTO glass was ultrasonically treated with detergent, anhydrous ethanol and deionized water for 15 minutes, respectively, and then dried with compressed air. Nickel acetylacetonate powder was dissolved in acetonitrile solution at a concentration of 0.2 mol / L, stirred for 6 hours to completely dissolve it, and filtered before use to obtain a transparent and uniform precursor solution. The FTO glass treated with an ozone cleaner was placed on a hot table. After the temperature rose to the set temperature, the precursor solution was poured into the nozzle, the nitrogen bottle pressure reducing valve was adjusted to 0.15 MPa, the height of the nozzle from the FTO glass surface was maintained at 15~20 cm, and the solution was evenly sprayed on a 10 × 10 cm 2 After spraying, the FTO area was annealed at the original temperature for 30 min, cooled to room temperature and removed for standby use to obtain the NiO hole transport layer. A perovskite film was prepared on the surface of the NiO hole transport layer according to the method of Example 1; The substrate coated with NiO and perovskite film was placed in a vacuum coating equipment, the vacuum degree was drawn to 2*10-4Pa, and C60 was deposited at a rate of 0.1Å / s with a thickness of 30 nm; then the barrier layer BCP was deposited at a rate of 0.1Å / s with a thickness of 10 nm; finally, the silver electrode was deposited at a rate of 1Å / s with a thickness of 100 nm, to obtain a C60 electron transport layer, a BCP barrier layer and an Ag electrode stacked in sequence.
[0039] Example 3 A perovskite battery, the other contents are the same as those of Example 2, except that the amount of serine used is 94.6 mg.
[0040] Example 4 A perovskite battery, the other contents are the same as those of Example 2, except that the amount of serine used is 126.1 mg.
[0041] Example 5 A perovskite battery, the other contents are the same as those of Example 2, except that the amount of serine used is 189.0 mg.
[0042] Example 6 A perovskite battery, the other contents are the same as those of Example 2, except that serine is replaced by alanine.
[0043] Example 7 A perovskite battery, the other contents are the same as those of Example 2, except that serine is replaced by valine.
[0044] Example 8 A perovskite battery, the other contents are the same as those of Example 2, except that serine is replaced by leucine.
[0045] Example 9 A perovskite film, other contents are the same as those of Example 1, except that the precursor solution is directly coated on a soda-lime glass substrate instead of a FTO|NiO substrate.
[0046] Comparative Example 1 A perovskite film, the other contents are the same as those in Example 1, except that the preparation steps are as follows: Weigh 691.5 mg of lead iodide powder, dissolve it in a mixed solution of 800 μL of DMF and 200 μL of DMSO, and continue to shake on an oscillator for more than 2 hours to completely dissolve it, thereby obtaining a precursor solution; The precursor solution was coated on the FTO|NiO substrate at a coating speed of 10 mm / s and a distance between the blade and the substrate of 150 μm. Then, the substrate coated with the precursor was annealed on a hot plate at 100°C for 20 min to obtain a crystalline lead iodide film.
[0047] Weigh 158.8 mg of FAI, 18.5 mg of MABr and 18.2 mg of MACl powder respectively, dissolve them in 1 mL of IPA solution, and continue to oscillate in an oscillator for 25 minutes to completely dissolve them to obtain an organic halide ammonium salt solution, which is coated on the crystalline lead iodide film at a coating speed of 15 mm / s and a distance of 200 μm between the blade and the substrate. Then, anneal the substrate on a hot plate at 150°C for 30 minutes to obtain a perovskite film.
[0048] Comparative Example 2 A perovskite solar cell, whose structure is FTO|NiO|perovskite layer|C60:BCP|Ag; the perovskite layer is the perovskite film of comparative example 1.
[0049] Comparative Example 3 A perovskite film, other contents are the same as those of comparative example 1, except that the perovskite film is deposited on a soda-lime glass substrate instead of a FTO|NiO substrate.
[0050] Test and Evaluation 1. Photovoltaic performance test of perovskite solar cells The perovskite solar cells obtained in Examples 2-5 and Comparative Example 2 were subjected to performance tests.
[0051] Test conditions: The light intensity of simulated sunlight is 1000 W m -2 , add an effective area of 0.16cm on the top of the battery 2 The test results are shown in Table 1.
[0052] Table 1 Performance test results of perovskite solar cells prepared in Examples 2-5 and Comparative Example 2
[0053] Note: All parameters in the table are positive scan.
[0054] As can be seen from Table 1, in the preparation of the perovskite film in Comparative Example 2, no serine was added, and the crystalline dense lead iodide film formed a strong diffusion barrier, which hindered the diffusion of the organic ammonium salt to the bottom of the lead iodide, resulting in incomplete reaction of the organic ammonium salt with the lead iodide, and the quality of the formed perovskite film was poor, so the device efficiency was also low, only about 19.22%. In Examples 2-5, different amounts of serine were added, and serine reacted with lead iodide to form an amorphous (amino acid) 2 PbI 2 Template, then by high temperature annealing, serine gasification, leaving a loose disc-like amorphous lead iodide film with interpenetrating nanopores. Organic ammonium salts interpenetrate each other through these nanopores, achieve complete reaction with amorphous lead iodide, and form a dense perovskite film with high crystallinity. Therefore, embodiment 2-5 has a greater improvement in device performance relative to comparative example 2. In particular, when the mass of serine is 157.6mg, the device efficiency can reach 23.7%. In embodiment 2-5, the improvement in perovskite device performance is caused by the improvement in perovskite film quality and the reduction in defects. It can be seen that amorphous lead iodide with loose disc-like interpenetrating nanopores can induce organic ammonium salts to react completely, forming a dense, high-quality perovskite film, thereby achieving a higher photoelectric conversion efficiency.
[0055] In addition, the performance of the perovskite solar cells obtained in Examples 2, 6-8 and Comparative Example 2 was tested.
[0056] Test conditions: The light intensity of simulated sunlight is 1000 W m -2 , add an effective area of 0.16cm on the top of the battery 2 The test results are shown in Table 2.
[0057] Table 2 Performance test results of perovskite solar cells prepared in Examples 2, 6-8 and Comparative Example 2
[0058] Note: All parameters in the table are positive scan.
[0059] The experimental results in Table 2 show that different types of amino acids can form amorphous (amino acids) with lead iodide. 2 PbI 2 template, thereby leaving a loose disk-like amorphous lead iodide film with interpenetrating nanopores after the first annealing, which helps to form a dense and highly crystalline perovskite film, thereby improving the performance of the device.
[0060] 2. Morphology test The perovskite film samples prepared in Comparative Example 1 and Example 1 were subjected to morphological tests (SEM), and the results are as follows: Figure 2 shown.
[0061] from Figure 2 It can be seen that the surface morphology of the perovskite light-absorbing layer prepared based on crystalline lead iodide in Comparative Example 1 is poor, the surface is relatively rough, and there are a large number of unreacted lead iodide particles; while the grains in the perovskite light-absorbing layer prepared based on amorphous lead iodide in Example 1 are full and uniform, the grain boundaries are clear, and the surface is smooth; the above results indicate that amorphous lead iodide can reduce the diffusion barrier of organic ammonium salts, which is conducive to complete reaction with ammonium salts to form a dense, highly crystalline perovskite film.
[0062] 3. Steady-state fluorescence test The perovskite film samples prepared in Comparative Example 3 and Example 9 were subjected to steady-state fluorescence tests. The results are as follows: Figure 3 shown.
[0063] from Figure 3 It can be seen that in Comparative Example 3, due to the poor crystallization quality of the perovskite film, there are a large amount of unreacted lead iodide and a large number of defects, which leads to strong non-radiative recombination, making its PL intensity much lower than that of Example 9; the above results show that amorphous lead iodide can induce the formation of a perovskite film with fewer defects and less surface non-radiative recombination.
[0064] 4. Stability test of perovskite solar cells The perovskite solar cells prepared in Example 2 and Comparative Example 2 were subjected to a photodegradation test. The test conditions were: the light intensity was 100 mW·cm -2 The xenon lamp simulates sunlight. The test results are as follows Figure 4 shown.
[0065] from Figure 4 It can be seen that the photoelectric conversion efficiency of the perovskite solar cell prepared in Example 2 remained above 95% of the initial value in the photodegradation test within 2000h, showing excellent optical stability; while the photoelectric conversion efficiency of the perovskite solar cell prepared in Comparative Example 2 dropped to about 50% of the initial value after about 2000h. The above results show that the perovskite film prepared by the method in Example 2 has higher quality than that of Comparative Example 2, and significantly improves the photoinduced stability of the perovskite solar cell.
[0066] In summary, the present invention relates to a method for preparing a dense perovskite film from amorphous lead iodide and the application of the perovskite solar cell. The specific perovskite film preparation step is to mix an amino acid with lead iodide and add it to an organic solution, mix evenly, prepare a precursor solution, apply it on a substrate, and obtain a loose disc-shaped amorphous lead iodide film with interpenetrating nanopores after annealing; then, the organic ammonium salt is dissolved in isopropanol, and then applied on the amorphous lead iodide film, and after annealing on a heating table, a dense perovskite film with high crystallinity is obtained. The amino acid of the present invention is low in cost, the perovskite film preparation process is simple and easy to operate, and can be expanded to large-area components, which is conducive to promotion to other photovoltaic device fields.
[0067] The above specific implementations of the present invention do not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a perovskite film, characterized in that: The following steps are involved: S1. dissolving lead iodide and amino acid in an organic solvent to obtain a precursor solution; S2. coating the precursor solution on a substrate and performing a heat treatment to obtain an amorphous lead iodide film; S3. Applying an organic halide ammonium salt solution on the surface of the amorphous lead iodide film and performing a secondary heat treatment to obtain the perovskite film.
2. The method for preparing a perovskite thin film according to claim 1, characterized in that: The amino acids include one or more of alanine, valine, leucine, phenylalanine, serine, threonine, asparagine, glutamic acid, lysine, arginine, histidine, L-cysteine, glycine, and isoleucine.
3. The method for preparing a perovskite thin film according to claim 1, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
4. The method for preparing a perovskite thin film according to claim 1, characterized in that: The molar ratio of the amino acid to lead iodide is 0.3:1-3:
1.
5. The method for preparing a perovskite thin film according to claim 1, characterized in that: The temperature of the primary heat treatment is 160-400° C., and the time of the primary heat treatment is 10-300 min.
6. The method for preparing a perovskite thin film according to claim 1, characterized in that: The temperature of the secondary heat treatment is 60-180° C., and the time of the secondary heat treatment is 10-300 min.
7. The method for preparing a perovskite thin film according to claim 1, characterized in that: The organic halide ammonium salt includes one or more of FAI, MABr and MACl.
8. A perovskite film obtained by the preparation method according to any one of claims 1 to 7.
9. A perovskite solar cell comprising the perovskite film according to claim 8, characterized in that: It comprises a bottom electrode, a hole transport layer, the perovskite film as claimed in claim 8, an electron transport layer, a blocking layer and a metal electrode which are stacked in sequence.
10. The perovskite solar cell according to claim 9, characterized in that The hole transport layer comprises a nickel oxide layer; the electron transport layer is a C60 layer with a thickness of 10-50 nm; the barrier layer is a BCP layer with a thickness of 2-30 nm; and the metal electrode is Ag and / or Cu with a thickness of 80-180 nm.